Comparison of body mass index and physical activity levels of e-sportsmen - Başoğlu, Burhan (Frontiers in Public Health, 2025)
BackgroundThis study examines the relationship between body mass index (BMI) and physical activity levels in e-sports players. Focusing on the sedentary lifestyle and health risks associated with prolonged sitting and low physical activity, the study highlights critical challenges within the e-sports community.MethodsData was collected from 136 e-sports players on popular gaming platforms such as FIFA, Valorant, CS: GO and League of Legends. Physical activity levels were assessed using the International Physical Activity Questionnaire (Short Form) and participants’ health status was assessed using BMI classifications.ResultsThe results showed a significant inverse relationship between BMI and physical activity, with obese e-sports players having significantly lower activity levels and longer periods of sedentary behavior than their peers. Male e-sports players had higher levels of physical activity than females, reflecting biological, social and cultural factors that influence physical activity behavior.DiscussionThe study highlights the need for measures such as training programs, ergonomic adjustments and awareness campaigns to increase physical activity and reduce health risks among e-sports players. These findings provide valuable insights into the health effects of e-sports participation and emphasize the importance of promoting an active lifestyle to counteract the detrimental effects of prolonged sitting and inactivity. By filling gaps in the existing literature, this study contributes to the understanding of e-sports players’ health behaviors and offers practical recommendations for promoting healthier habits in this growing population.